THE RELATIONSHIP BETWEEN MATERNAL BEHAVIOR IN FEEDING AND NUTRITIONAL STATUS OF INFANTS 6-24 MONTHS OLD IN MARISA SELATAN VILLAGE OF MARISA SUB-DISTRICT, POHUWATO REGENCY: Doi: https://doi.org/10.47918/jhts.v3i1.334 - Sofyan Tambipi; Srikit S. Nurkamiden; Nova Dince Ntuiyo (Jurnal Ilmiah dr. Aloei Saboe, 2021)
The nutritional status of an infant and toddler is caused by the habit of parenting in daily life. It is also caused by eating habits or complementary foods that are not appropriate and not appropriate to the needs of infants and toddlers, especially children under 2 years. The present study aims to determine the relationship between maternal behavior in feeding the babies with the nutritional status of infants 6-24 months old in Marisa Selatan Village, Marisa District, Pohuwato Regency. The research method is cross-sectional because in this study the independent and dependent variables were observed at the same time. The research techniques carried out are surveys and direct observations in the field. The results show that most of the maternal knowledge in feeding the babiesis in the sufficient category, namely 39.3%, most of the maternal attitudes in feeding the babiesare in the positive category of 51.2%, and some of the maternal practices in feeding the babies with the category are less 70.2%. Most of the children aged 6-24 months have normal nutritional status, namely 65.5%. There is a relationship between the maternal knowledge of feeding the babies with the nutritional status of the child, there is no relationship between the maternal attitude in feeding the babies and the nutritional status of the child, and there is no relationship between the maternal practice of feeding and the nutritional status of the child.